Impact of COVID-19 on the lives and mental health of children and adolescents - Fengxiao Li (Frontiers Media S.A., 2022)
Student mental health is an integral part of the fight against disease, and health was an evolving concern during the spread of COVID-19. As the COVID-19 pandemic unfolds, physical distancing and social restrictions were introduced, and because of these, it was found a great impact on students' lives and their mental health. Adolescent mental health is focused on prevention, early detection, therapeutic innovation, and service development. In these circumstances, service providers can expand telemedicine Digital services that may help provide future mental health services to young people, particularly students. This study collects and analyzes data from students on the impact of these new online learning techniques, and by collecting and analyzing the challenges and issues faced by college students during the COVID-19 pandemic. The questionnaire was based on and extended the European Students' Union Survey and targeted higher education students concerning what student life looked like during the pandemic, including teaching and learning, their social contacts, habits/routines, as well as how they were coping with the situation emotionally and financially. The case of universities and distance learning education units in higher education during the COVID-19 pandemic process. This article highlighted the impact of COVID-19 on students of all ages and their time schedules such as online learning and reflection, study environment, sleep habits, routines, and outcomes. It was found that the students generally require greater self-discipline and motivation to complete online classes. It was also reflected that the pandemic adversely affected student mental health, leading to an increased prevalence of Major Depressive Disorder (MDD) and Generalized Anxiety Disorder (GAD). This may have a significant impact on their mental health issues such as frustration, stress, and sadness. This will significantly lead to cooperation between various local authorities and the private sector.